(untitled) (Actual Problems of Psychology in Educational Institutions, 2021)
This article examines the becoming of a system of leading functions for an exteroceptive level of organization. Exteroceptive means concerning the initial period of infancy, without taking into account its empirical specifics. As for the becoming, in addition to the considered level, the four previous ones are taken as a basis. And finally, the very content of becoming is derived from the configuration of the interaction cycles of the intra-level layers, which acts as a system of leading functions. Defining the ultimate goal for which the proposed scheme of analysis itself was created, it is seen as the basis for describing the exteroceptive organisation level.